Highly Efficient dc–dc Transformer Based on Multicell Converter Topology for Next Generation dc Distribution System. Issue 4 (March 2017) - HAYASHI, YUSUKE; TAKAI, DAIKI; MATSUMOTO, AKIRA; ISE, TOSHIFUMI
SUMMARY: A multicell dc–dc transformer (DCX) with an efficiency of 98.0% is developed for a next generation dc distribution system. Input series output parallel (ISOP) and input parallel output series (IPOS) connection topologies of highly efficient dc–dc cell converters have been applied to realize DCXs that have arbitrary I/O voltages and a high transfer factor. The behavior of a DCX based on multicell topology using nonregulated dc–dc converters is analyzed, and the voltage stress in each cell converter is discussed quantitatively considering the variation in converter circuit parameters. Further, the availability of the applied topology and the validity of the analysis are confirmed by fabricating a prototype of a 384 V to 12 V 2400 W DCX. The multicell topology contributes to realizing a low‐carbon society pushing the promotion of highly efficient, space‐saving, and low cost dc power supplies with standardized, highly efficient cell converter modules.